Relation between serum prolactin levels and antipsychotic response to risperidone in patients with schizophrenia. (30th June 2016) - Charan, Alladi; Shewade, Deepak Gopal; Rajkumar, Ravi Philip; Chandrasekaran, Adithan
Abstract: Background : Hyperprolactinemia is commonly seen in patients with schizophrenia on risperidone. Dopamine receptor blockade plays a major role in risperidone induced hyperprolactinemia. However, limited studies are available with inconsistent results on antipsychotic response to risperidone and prolactin elevation. Therefore, we aimed to study the change in serum prolactin levels and response to risperidone and to test the association between DRD2 genetic variants and prolactin levels in schizophrenic patients treated with risperidone. Methods : A prospective study comprising of 102 patients with schizophrenia were recruited. Prolactin levels and Positive and Negative Syndrome Scale (PANSS) score were recorded at baseline and after four weeks of risperidone treatment. Prolactin concentrations were measured by standard method Advia-Centaur® Chemiluminescence immuno assay method. Taq1A DRD2 genotyping was performed by qRT-PCR. Results : The mean±SD prolactin levels (ng/ml) were increased after four weeks of treatment in both responders (males 21.66±15.15 to 41.63±18.73; p<0.01 females 51.92±40.89 to 122.35±52.16; p<0.01) and non-responders group (males 23.89±14.85 to 37.45±13.5; p<0.01 females 39.25±26.94 to 91.13±54.31; p<0.01). Patients with increased prolactin concentration were 4.6 fold higher in responders (OR 4.60; 95%CI 1.376-15.389; p-value 0.01) compared to non-responders. Ninety-six patients were genotyped for Taq1A DRD2 gene (AA=9, AG=46, GG=41) and found no association (p=0.6) between genetic variants and response to risperidone. Conclusion : Patients were showing more than 20% increase in prolactin levels had a better chance of responding to risperidone therapy. Taq1A DRD2 gene did not show any association with prolactin elevation and response to risperidone. Highlights: Risperidone treatment significantly increases the serum prolactin levels after four weeks of medication. No significant difference in prolactin elevation in responders and non-responders to risperidone. Patients with increased (20%) prolactin concentration were four-fold higher in responder as compared to non-responder. Taq1A SNP of DRD2 is not associated with modulation of prolactin levels and clinical response to risperidone.